Dorothy was solving the following quadratic equation by factoring: `2x^{2}+7x-15=0`.

1 answer

To solve the quadratic equation \(2x^2 + 7x - 15 = 0\) by factoring, we can first look for two numbers that multiply to \(2 \cdot (-15) = -30\) (the product of the coefficient of \(x^2\) and the constant term) and add up to \(7\) (the coefficient of \(x\)).

The numbers that satisfy these conditions are \(10\) and \(-3\) since:

  • \(10 \cdot (-3) = -30\)
  • \(10 + (-3) = 7\)

Now, we can rewrite the middle term \(7x\) using these two numbers:

\[ 2x^2 + 10x - 3x - 15 = 0 \]

Next, we can factor by grouping:

  1. Group the first two terms and the last two terms: \[ (2x^2 + 10x) + (-3x - 15) = 0 \]

  2. Factor out the common factors in each group: \[ 2x(x + 5) - 3(x + 5) = 0 \]

  3. Now, factor out the common binomial factor \((x + 5)\): \[ (2x - 3)(x + 5) = 0 \]

Now, we can set each factor equal to zero to find the solutions:

  1. For \(2x - 3 = 0\): \[ 2x = 3 \implies x = \frac{3}{2} \]

  2. For \(x + 5 = 0\): \[ x = -5 \]

Thus, the solutions to the quadratic equation \(2x^2 + 7x - 15 = 0\) are: \[ x = \frac{3}{2} \quad \text{and} \quad x = -5 \]